What Do Young People Want to Know about Sex, and Where Do They Look for Answers? Case Study of Poland - Bilarzewska, Julia; Grunt-Mejer, Katarzyna; Ladra, Sara; Neter, Julia; Marciniak, Izabela (Podstawy Edukacji, 2024)
The survey included 341 people aged 18–30 who answered the following questions: What sex-uality-related question have you wanted answered recently? Were you able to get an answer to this question? Where did you try to find the answer to your question? The sources of knowledge about sexuality that the respondents valued were also checked. The responses were subject to thematic analysis. Analysis of the responses revealed five major topics containing 39 themes. The topics were sexual health (the most frequently sought answers concerned contraception, physiology and anatomy), sexual activity (the most frequent question concerned anal sex), sexual pleasure (the most frequent theme concerned orgasm), psychology and relationships (the most frequent theme concerned the quality of desire and sex in long-term relationships), and socio-cultural knowledge (the dominant theme concerned genderidentity and sexual orientation). The most common source of knowledge is the Internet, mainly social media. The results indicate a significant need for even elementary education on anatomy, physiology and contraception. Questions related to the impact of pornography and the need for respondents to understand rapid social changes, including diverse orientations and identities, are also prevalent.